2015
DOI: 10.1530/joe-15-0451
|View full text |Cite
|
Sign up to set email alerts
|

The pituitary TGFβ1 system as a novel target for the treatment of resistant prolactinomas

Abstract: Prolactinomas are the most frequently observed pituitary adenomas and most of them respond well to conventional treatment with dopamine agonists. However, a subset of prolactinomas fails to respond to such therapies and is considered as dopamine agonist-resistant prolactinomas (DARPs). New therapeutic approaches are necessary for these tumors. TGFβ1 is a known inhibitor of lactotroph cell proliferation and prolactin secretion, and it partly mediates dopamine inhibitory action. TGFβ1 is secreted to the extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 111 publications
(122 reference statements)
1
33
0
1
Order By: Relevance
“…The data reported in this study (summarized in Fig. 8), together with former observations from us and several other groups [2, 39, 51, 54-57], support a new concept for the pathogenesis of prolactinomas. We suggest that PRLR signaling, involving the PRLR per se or effectors thereof, may favor a state of PRL resistance resulting in the downregulation of proapoptotic and antiproliferative effects that are mandatory for pituitary homeostasis, thereby promoting tumor development.…”
Section: Discussionsupporting
confidence: 87%
“…The data reported in this study (summarized in Fig. 8), together with former observations from us and several other groups [2, 39, 51, 54-57], support a new concept for the pathogenesis of prolactinomas. We suggest that PRLR signaling, involving the PRLR per se or effectors thereof, may favor a state of PRL resistance resulting in the downregulation of proapoptotic and antiproliferative effects that are mandatory for pituitary homeostasis, thereby promoting tumor development.…”
Section: Discussionsupporting
confidence: 87%
“…Many studies have shown that targeting some high-frequency hub-molecules in Table 1 has achieved good results in other types of pituitary adenomas. For example, TGFβ1 is used as a novel therapeutic target to treat resistant prolactinomas (66); the microRNA-145 inhibits the activation of the mTOR signaling by targeting AKT3 to suppress the proliferation and invasion of invasive pituitary adenoma cells (67); lncRNA H19 inhibits mTORC1 by disrupting 4E-BP1/Raptor interaction in pituitary tumors (68); and MAPK Pathways act as therapeutic targets in pituitary tumors (69). Because PI3K/Akt/mTOR and ERK/MAPK signaling pathways are significantly dysregulated in NFPA, and these two essential signaling pathways are not only related to rapid proliferation and apoptosis resistance of tumor cells, but also can regulate the activities of many other pathways and then regulate tumor growth in the multiple levels.…”
Section: Mapk Pathways Were Dysregulated In Nfpasmentioning
confidence: 99%
“…The importance of TGFβ1 in inhibiting lactotroph function is clearly demonstrated by the fact that in human prolactinomas, as well as in animal models of prolactinomas, the TGFβ1 expression and activity were found reduced, suggesting its involvement in the tumor development (Pastorcic et al 1995, Recouvreux et al 2011, 2016.…”
Section: Introductionmentioning
confidence: 99%